An educational strategy for combating moral degeneration in South African society - De Klerk-Luttig, J; Van der Walt, JL (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
The authors’ study of the insidious problem of moral decay in South Africa and of the anatomy of religion and of spirituality leads them to contend that one of the most effective strategies for combating the problem of moral degeneration in South African society and schools will be the reintroduction of confessional religion (and spirituality) in the public (state) schools. Their contention is validated by four arguments. The reintroduction of confessional religious education in schools might, however, lead to inter-religious conflict. The problem can be pre-empted if educators (teachers) were adequately prepared for this specific form of education.